Therapeutic drug monitoring of sertraline and clinical response - Y. W. Francis Lam (The Brown University Psychopharmacology Update, 2026)
Variability in drug exposure and response among individual patients can occur because of numerous factors, including age, sex, metabolic capacity, medication adherence, and the presence and magnitude of interactions with concurrently administered drugs. For decades, therapeutic drug monitoring with drug concentration determinations has been used to evaluate whether variability in drug exposure might be related to significant differences in therapeutic response to psychotropics (Hart et al., 2024; Kang & Lee, 2009).